MEMBANGUN SUKSES DI ERA 4.0 DAN SOCIETY 5.0: DAMPAK TEKNOLOGI INFORMASI DAN SOFT SKILL TERHADAP KINERJA KARYAWAN - Maharani, Hemas Citra (Jurnal Ekonomi dan Bisnis, 2024)
The dynamics of information technology in the era of the industrial revolution require professionals to update information technology and be supported by soft skills based on artificial intelligence-AI. This research uses primary data by distributing questionnaires via Google Form. The research population involved employees of PT. Indonesia Vapor Group which uses one of the several software applications available such as Oracle HCM; Bamboo HR; Salesforce Marketing Cloud; Google Analytics; and HubSpot. The selected sample was 155 using purposive sampling technique. The research results show that information technology knowledge and soft skills have a significant impact on employee performance. These results provide a comprehensive picture to lead to practical implications in human resource management and employee development in the future work environment.